Insight into the machinery that oils chromatin dynamics. (1st November 2016) - Wright, Roni H. G.; Fernandez-Fuentes, Narcis; Oliva, Baldomero; Beato, Miguel
ABSTRACT: The packaging of genetic information in form of chromatin within the nucleus provides cells with the ability to store and protect massive amounts of information within a compact space. Storing information within chromatin allows selective access to specific DNA sequences by regulating the various levels of chromatin structure from nucleosomes, to chromatin fibers, loops and topological associating domains (TADs) using mechanisms that are being progressively unravelled. However, a relatively unexplored aspect is the energetic cost of changing the chromatin configuration to gain access to DNA information. Among the enzymes responsible for regulating chromatin access are the ATP-dependent chromatin remodellers that act on nucleosomes and use the energy of ATP hydrolysis to make chromatin DNA more accessible. It is assumed that the ATP used by these enzymes is provided by the mitochondria or by cytoplasmic glycolysis. We hypothesize that though this may be the case for cells in steady state, when gene expression has to be globally reprogramed in response to externals signals or stress conditions, the cell directs energy production to the cell nucleus, where rapid chromatin reorganization is needed for cell survival. We discovered that in response to hormones a nuclear ATP synthesis mechanism is activated that utilizing ADP-ribose and pyrophosphate as substrates. 1 This extra view aims to put this process within its historical context, to describe the enzymatic steps in detail, to propose a possible structure of the ATP synthesising enzyme, and to shed light on how this may link to other reactions within the cell providing a perspective for future lines of investigation.